Analisis Pengaruh Fouling dan Slagging Terhadap Kinerja Boiler Subcritical pada PLTU Moramo - Inaswara, Fadhilla; Sudia, Budiman; Sisworo, Raden Rinova (Teknik Mesin Universitas Halu Oleo, 2021)
Boilers that use low-quality coal result in an increase in the amount of coal burning and the high formation of accumulated ash deposits (fouling and salgging). It is necessary to conduct research the effect of fouling and slagging on boiler efficiency in steam power plant Moramo for the boiler performance improvement purpose. The objective of this research are identified fouling and slagging and how its affect boiler performance. By using the principle of mass and energy balance, heat transfer in the evaporator and superheater areas are used as the basis for identifying slagging and fouling. Boiler efficiency is calculated by a direct method. An increase in flue gas temperature which is affected by a degradation in the rate of heat transfer indicates the formation of slagging and fouling. Boiler efficiency is related to the slagging index and sodium content in the ash of coal, the result of higher slagging index and lower the sodium content will further increase boiler efficiency. The best average efficiency of boiler is 89.853% when coal from supplier Y used as fuel with slagging index value is 2370.2 and sodium content in ash is 0.48%..Keyword: Fouling, slagging, heat transfer, efficiency, boiler